PENGARUH PENGGUNAAN MEDIA BIG BOOK BERBASIS DIGITAL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Maula Ishak; Andi Paida; Nur Khadijah Razak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using digital-based Big Book media on the reading comprehension ability of fourth grade students at SD Muhammadiyah Perumnas Makassar. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest design. The subjects of this study were 20 fourth grade students. Data were collected through reading comprehension tests administered before and after the implementation of digital Big Book media. The results showed that students’ reading comprehension ability improved after the use of digital Big Book media in the learning process. The average score of students in the pretest was 55.30, while the average score in the posttest increased to 82.45. This result indicates a significant improvement in students’ reading comprehension skills after the implementation of the media. The use of digital-based Big Book media helps students understand the content of reading texts more easily through clear text and attractive visual illustrations. Therefore, digital Big Book media can be used as an effective learning medium to improve reading comprehension skills of elementary school students.